World Heritage of Istanbul from Perspective of Vernacular Architecture - Kambek, Erkan (Actual Problems of Theory and History of Art, 2024)
Istanbul, strategically situated between Europe and Asia on the Bosphorus Peninsula, has served as a hub of political, religious, and artistic significance for over two millennia. The city is home to four distinct areas inscribed as the “Historical Areas of Istanbul” on the UNESCO World Heritage list: the Archaeological Park, the Süleymaniye Quarter with its iconic mosque complex and surrounding bazaars, the Zeyrek area centered around the Zeyrek Mosque, and the Theodosian land walls region, once home to the Blachernae Palace. Despite their historical and cultural value, these heritage sites face significant threats from population growth, industrial pollution, and unchecked urbanization. This paper focuses on the challenges confronting the vernacular wooden architecture of the Süleymaniye Quarter, an area where monumental structures often overshadow the more vulnerable civil architectural heritage. Although Istanbul’s city center has been free of serious conflicts for centuries, the Süleymaniye Quarter bears the appearance of a conflict zone, grappling with issues such as tourism pressures, urban development, neglect, and mismanagement. International guidelines suggest that reconstruction of historical centers is warranted only after wars or natural disasters. Yet, the Süleymaniye Quarter faces a gradual decline rooted in evolving legal regulations and urban policies. This paper seeks to uncover the underlying causes of decay in the area and explores how to address the social, cultural, and architectural deterioration that has emerged without the presence of an explicit conflict.The study is grounded in a comprehensive review of local research conducted over the past two decades, aimed at understanding the approaches taken to preserve the Süleymaniye Quarter. Additionally, site investigations have been conducted to assess the authenticity of the area’s architectural heritage, particularly as many vernacular buildings have been reconstructed over time rather than preserved in their original form. The analysis also incorporates the latest findings from the Istanbul Metropolitan Municipality’s on-site evaluations. Preserving the invaluable heritage of the Süleymaniye District is a race against time. Situated in a seismically active region, Istanbul faces a high probability of a major earthquake within the next two decades. Protecting the district’s fragile wooden structures requires immediate action, not only to strengthen their physical resilience but also to address the social and economic vulnerabilities intensified by earthquakes, population pressures, industrial pollution, and uncontrolled urban growth.
Keywords: Süleymaniye quarter; timber vernacular architecture; UNESCO World Heritage; cultural heritage conservation; heritage preservation strategies; reconstruction and authenticity